“No Chit Chat!” A Warning From a Physical Versus Virtual Robot Invigilator: Which Matters Most? - Ahmad , Muneeb I.; Refik , Reem (Frontiers in Robotics and AI, 2022)
Past work has not considered social robots as proctors or monitors to prevent cheating or maintain discipline in the context of exam invigilation with adults. Further, we do not see an investigation into the role of invigilation for the robot presented in two different embodiments (physical vs. virtual). We demonstrate a system that enables a robot (physical and virtual) to act as an invigilator and deploy an exam setup with two participants completing a programming task. We conducted two studies (an online video-based survey and an in-person evaluation) to understand participants’ perceptions of the invigilator robot presented in two different embodiments. Additionally, we investigated whether participants showed cheating behaviours in one condition more than the other. The findings showed that participants’ ratings did not differ significantly. Further, participants were more talkative in the virtual robot condition compared to the physical robot condition. These findings are promising and call for further research into the invigilation role of social robots in more subtle and complex exam-like settings.